Dietary manipulation of rumen microorganisms for efficient ruminant production - Sevilla, Cesar C. (2011)
Interest in exploring the rumen ecology of tropical ruminants has been increasing for two reasons, namely to increase the utilization of lignocellulolytic feed materials for better productivity and to search for novel, beneficial microbial species that may reside in the rumen of tropical ruminants fed low quality roughage. There is still a paucity of knowledge on rumen ecology with regards to microbial interactions, consortium formation synergism and cross feeding. While the theoretical basis for optimum nutrition of tropical ruminants has been widely accepted, the approaches wherein the rumen microorganisms can be manipulated to further improve rumen fermentation have not yet been fully understood and utilized. This is due to the high complexity of the rumen ecology. Based on the research results reviewed and the limited local work done on native ruminants, there is a bright prospect in manipulating rumen ecology using natural feed resources.
Keywords: Rumen fermentation; Ruminants -- Feeding and feeds